Exploring Text Messages by Using Emojis on Indonesian Whatsapp - Sholihatul Hamidah Daulay; Hotma Berutu (JALL (Journal of Applied Linguistics and Literacy), 2023)
WhatsApp is a free messaging and calling application that can be downloaded to mobile phones all over the world that supports the feature. It is straightforward, trustworthy, and secure. WhatsApp enables us to exchange text, voice, and audio-visual (video) messages. However, text message recipients often fail to understand the intended meaning of a text message because the text messages are not provided with intonation and direct expression, resulting in the recipient’s difficulty interpreting the message's intended meaning. This study aimed to find out the functions of emojis in WhatsApp text messages. Interpretative qualitative was used as the research methodology in this study. The data source used is the results of screenshots of chat activities on the WhatsApp application. The study came up with the findings that the primary function of emojis in WhatsApp text messages is to show and emphasize emotion, expression, and feeling like happiness, sadness, apology, embarrassment, support, anger, mockery, gratitude, criticism, humorous, etc. that cannot be spoken verbally or conveyed/shown directly.